Introduction: rethinking protohistories: texts, material culture and new methodologies. Issue 5 (20th October 2018) - Foxhall, Lin
ABSTRACT: This introduction problematizes the use of the term protohistory across a wide range of cultures and periods. The methodological issues surrounding periodization and the integrated use of different, multiple evidence streams is discussed, especially the difficulties of combining material and textual data, and how we as archaeologists can best construct narratives.